Samspelet mellan text och bild i illustrerade ordböcker - Lampinen, Kati (Nordiske Studier i Leksikografi, 2010)
The aim of this article is to discuss the interaction between text and image in illustrated dictionaries and to present an example on how this interaction might be investigated. As the interaction of the modalities is crucial for the usability of illustrated dictionaries, it is important to study how the verbal and the visual convey meanings together. This article starts with an overlook on four different Swedish dictionaries with emphasis on the role of illustrations in them, as well as the composition of the entries with references to these aspects in Svensén (2004). The article ends with an example analysis of an entry in Norstedts första svenska ordbok, and the analysis is based on the meaning of composition presented by Kress & van Leeuwen’s visual grammar Reading Images (2006). Special emphasis is put on the concepts information value and salience.